Kajian Yuridis Terhadap Pertimbangan Hakim Dalam Tindak Pidana Pemerasan Terhadap Pengusaha Real Estate Indonesia (REI) di Provinsi Nusa Tenggara Timur (Studi Kasus Putusan Pengadilan Negeri Kelas IA Kupang Nomor : 40/Pid.Sus/2022/PN.Kpg) - Ysmiralda, Samantha; Kadja, Thelma; Fallo, Debby (Artemis Law Journal, 2024)
The Judge’s Consideration is defined as a stage where the panel of judge’s considers the facts revealed during the trial process which are connected to evidence that meets the formal and material requirements presented in the plea evidence. The problem formulation in this research is (1) How is the application of material criminal law in decision number 40/Pid.Sus/2022/PN.Kpg? (2) What is the basis for the judge’s considerations in handing down a criminal decision for the defendant in accordance with the decision in case number 40/Pid.Sus/2022/PN.Kpg? In this study, the Author used Normative Juridical Legal Research Methods. The results showed (1) According to the Authors in this case, of course, not only the recipient has the potential to become a suspect, but the Bribe Giver can also be used as a suspect, but it seems like there is an effort to protect the Indonesian Real Estate NTT (REI). (2) The basis for the Judge’s Considerations is based on the public prosecutor demands and taking into account the evidence presented by The Public Prosecutor also paid attention to the defense submitted by defendant legal advisor.